Characterization of Eu-doped Ba2SiO4, a high light yield scintillator. (9th November 2020) - Nakauchi, Daisuke; Kato, Takumi; Kawaguchi, Noriaki; Yanagida, Takayuki
Abstract: Photoluminescence and scintillation characteristics of Eu-doped Ba2 SiO4 were investigated. A broad emission band due to Eu 2+ is observed at 500 nm, and the photoluminescence and radioluminescence decay time constants are about 397 and 515 ns, respectively. From the pulse height distribution of 57 Co γ -rays, the light yield of Eu:Ba2 SiO4 is ∼48 000 ph MeV −1, which is comparable with those of developed oxide scintillators showing a high light yield. The results demonstrate that Eu-doped Ba2 SiO4 is a high-performance scintillator for X- and γ -ray measurements and characterized by excellent scintillation output and afterglow.